Planning and Sizing of Electrical Networks of Underground Distribution by Metaheuristic Method (2019)
The introduction of new loads to the traditional electrical distribution systems can lead to the overloading in the power equipment. This on the sizing makes the useful life of the power equipment decrease considerably, in addition, the reliability and stability of the system begins to be compromised. Therefore, through the present investigation it is possible to solve the problem of the planning of electrical distribution networks by integrating the possibility of migrating from the concept of traditional electric networks to smart electric networks, the same ones that only electrical distribution systems of robust networks are achieved heterogeneous bidirectional communication. The present work focused on the development of a model capable of locating the distribution transformers in the best sites to satisfy the majority of users of the electrical network and obtain the best topology by applying the theory of graphs In addition, the presented model contemplates the development of a heuristic capable of executing georeferenced planning processes through the management and use of geolocated information from OpenStreetMap through the .osm file that this free platform offers us. The heuristic proposed in the present document is modeled using the Matlab software and to validate the information, the Cymdist software is required.